Needs Analysis Teaching Materials of STEAM Approach in Innovative Learning Courses - Agus Santoso; Khoiro Mahbubah; Sendi Faisal Alim (South Sulawesi Education Development (SSED), 2024)
The need for teaching materials and the limited availability of teaching materials in universities encourage lecturers to constantly innovate in developing teaching materials for lectures. This research aims to obtain information about the need for teaching materials with a STEAM approach in innovative learning courses. This type of research is descriptive qualitative. The sample used involved 25 students of the science education study program using purposive sampling. The data obtained included needs analysis, semester learning plan analysis, and teaching material analysis. The data collection technique for needs analysis used a percentage questionnaire and interviews to describe the data. In contrast, data regarding semester learning plan analysis and teaching material analysis were obtained through observation. Before the study was conducted, the instrument was validated with a score of 92.7 in the very feasible category. The results of the study: 1) Innovative teaching materials with a STEAM approach are needed with a score of 88.5% (very needed category). 2) The available teaching materials are limited, so the development of STEAM-approach teaching materials is needed where this learning is still relatively new and in accordance with innovative learning. 3) The semester learning plan for innovative learning courses supports the development of STEAM-approach teaching materials.